La circulation, la ville et l’urbanisme : de la technicisation des transports au concept de mobilité. - Gérard Beaudet; Pauline Wolff (VertigO, 2012)
Urban transportation has always been a major issue in cities. Therefore it is no suprise to learn that transport has remained a major focus within the field of Urban Planning since the field's conception in the mid-19th century. Largely due to the fascination with technique and rational decision-making emerging in the first half of the twentieth century, matters of transportation were taken on primarily by engineers, thereby distinguishing and separating transport from land-use planning. Despite caution from both professionals and citizens throughout the century, the importance of transportation was often emphasized and prioritized over the importance of land use. Using the Montreal metropolitan area as an example, this article aims to show how this historical bias in favour of transport might assit in explaining the limits of the ‘supply and demand’ approach in transportation. Nevertheless, the emergence of the so-called ‘mobility paradigm’ will hopefully enable us to reconstruct the necessary connection between urban planning and transportation.